Pengaruh Penggunaan Batu Kapur dari Wilayah Sampung Kabupaten Ponorogo Sebagai Pengganti Agregat Kasar Terhadap Kuat Tekan Beton - Mahanani, Aulia Bintang; Rochmah, Nurul (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
Ponorogo, renowned for its abundant mineral resources such as limestone, presents an opportunity to utilize this material as a substitute for coarse aggregate in concrete mixtures. This research investigated the impact of replacing coarse aggregate with Sampung limestone at concentrations of 0%, 25%, 50%, 75%, and 100%. Following the Department of Environment (DoE) method and referencing SNI 03-2834-2000 for concrete mix design, 28-day compressive strength tests yielded results of 14.35 MPa for 0% limestone, 12.96 MPa for 25%, 14.35 MPa for 50%, 12.03 MPa for 75%, and 10.65 MPa for 100%. Remarkably, the findings indicate that the 50% limestone mixture achieved the most optimal compressive strength.